The root-knot nematode effector MiMSP32 targets host 12-oxophytodienoate reductase 2 to regulate plant susceptibility - Verhoeven, Ava (The New phytologist, 2023)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.